Complete Genome Sequence Analysis of Bacillus subtilis MC4-2 Strain That against Tobacco Black Shank Disease - Chunlan Shi; Shuquan Zeng; Xi Gao; Mehboob Hussain; Mingchuan He; Xurong Niu; Congcong Wei; Rui Yang; Mingxian Lan; Yonghui Xie; Zhijiang Wang; Guoxing Wu; et al. (International Journal of Genomics)
The MC4-2 bacterium strain was isolated and purified from the Periplaneta americana intestine as a biocontrol agent with good antagonistic effect against the pathogens of a soil-borne disease called tobacco black shank. The MC4-2 strain was found to have good broad-spectrum inhibition by plate stand-off test. Based on 16S rRNA and gyrB genes, ANI analysis, and other comparative genomics methods, it was determined that the MC4-2 strain was Bacillus subtilis. The complete genome sequence showed that the genome size was 4,076,630 bp, the average GC content was 43.78%, and the total number of CDSs was 4,207. Genomic prediction analysis revealed that a total of 145 genes were annotated by the CAZy, containing mainly GH and CE enzymes that break down carbohydrates such as glucose, chitin, starch, and alginate, and a large number of enzymes involved in glycosylation were present. A total of ten secondary metabolite clusters were predicted, six clusters of which were annotated as surfactin, bacillaene, fengycin, bacillibactin, subtilosin A, and bacilysin. The present investigation found the biological control mechanism of B. subtilis MC4-2, which provides a strong theoretical basis for the best use of this strain in biological control methods and provides a reference for the subsequent development of agents of this bacterium.